On the fractional moments of a truncated centered multivariate normal distribution - Ogawa, Mitsunori; Nakamoto, Kazuki; Sei, Tomonari (Communications in statistics. Simulation and computation, 2022)
In this paper, we study the fractional moments of a truncated centered multivariate normal distribution, with a focus on their computation. We develop computational methods, including ones based on the holonomic gradient method, the second-order Laplace approximation, and the Monte Carlo method. These methods enable us to compute higher order fractional moments without evaluating multiple integrals. Via numerical experiments, we investigate their performances. Some applications, including robust graphical modeling based on the alternative multivariate t-distribution, are also presented.